Do Social Capital Have Impact on Willingness to Pay for Waste Management? Evidence from Contingent Valuation Studies - Saptutyningsih, Endah; Bilqis , Nada (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This study looks at the connection between people’s willingness to pay (WTP) for waste management services anf their social capital. The research utilitizes a linier regression model to examine the relationship between social capital and people’ desire to interact, making use of contigent valiation, a technique useful for assessing financial prices and preferences for non-market environmental assets. With an average WTP of IDR 17,000 (USD 1,09), the result show that 58.2% of the community is willing to pay for garbage management. The study finds a positive correlation between social capital and WTP, suggesting that strong community bonds, high levels of trust, and external family connections enhance the likelihood of supporting sustainable waste management initiatives. In addition to sociodemographic traits, the WTP's ability to manage waste is also impacted. Legislators and waste management experts should take note of these findings, which emphasize the need of fostering social capital to boost public involvement and support for sustainable waste management projects. Building trust, promoting community involvement, and establishing shared environmental principles can all contribute to the development of an environment that is conducive to effective waste management techniques. This study contributes to the expanding body of information about the socioeconomic drivers of waste management practices by highlighting the crucial role that social capital plays in creating WTP for waste management solutions.